Teacher’s and Students’ Attitudes Toward the Indonesian Language in Learning Interaction at Senior High School - Ammar Faqih Utomo; Dini Restiyanti Pratiwi (English Department, Universitas Negeri Surabaya, 2026)
The teaching of Indonesian language plays an important role in shaping positive attitudes toward the Indonesian language. This study aims to analyse the language loyalty, language pride, and awareness of the norm attitudes of teachers and students in classroom learning interaction using a descriptive qualitative approach. Data were collected through non-participatory observation, audio recording, and note-taking, and subsequently analysed using the Miles, Huberman, & Saldana model with theory and source triangulation as validity measures. The findings of this study indicate that the teacher and students of Class XI-5 at SMA Muhammadiyah 1 Surakarta have (1) demonstrated language loyalty attitudes reflected in the consistent use of Indonesian as the primary medium of learning, the minimal use of elements from other languages in formal academic contexts, and the absence of language switching in the delivery of substantive subject matter, (2) demonstrated positive language pride attitudes toward Indonesian reflected in the confident use of Indonesian as a symbol of academic identity across all domains of formal learning, without any tendency to switch to other languages considered more prestigious, as well as the ability to distinguish between the use of Indonesian as a marker of national identity and Javanese as a marker of local identity in a coexisting manner, and (3) demonstrated language norm awareness attitudes reflected in the appropriate use of academic vocabulary in accordance with the formal register in the delivery of learning materials, although the application of standard language norms at the level of sentence structure and grammatical consistency has not yet been fully optimal, particularly in spontaneous oral speech on the part of both the teacher and students.